Do Workers from Subspecies Acromyrmex subterraneus Prepare Leaves and Toxic Baits in Similar Ways for Their Fungus Garden? - Forti, L. C. [UNESP]; Andrade, A. P. P. [UNESP]; Sousa, K. K. A. [UNESP]; Camargo, R. S. [UNESP]; Matos, C. A. O. [UNESP]; Caldato, N. [UNESP]; Catalani, G. C. [UNESP]; Ramos, V. M. (Entomological Soc Brasil, 2020)
Toxic baits are the most efficient method to control leaf-cutter ants in eucalyptus forests for paper and cellulose production. For the proper use of these baits, insecticide compounds must reach workers and contaminate them. Thus, understanding how these baits are processed inside the nests is vital for a successful control, especially when it comes to genus Acromyrmex. Lack of information on toxic baits and on contamination of Acromyrmex workers raises the question: do workers from subspecies Acromyrmex subterraneus (Forel) prepare leaves and toxic baits in similar ways for their fungus garden? To answer it, this study described and analyzed the behavioral repertoire executed by A. subterraneus workers during the preparation of leaf disks and baits and their incorporation into the fungus garden. Results show that the act of licking the substrate was the most frequently executed behavior, regardless of subspecies or size categories. Moreover, additional behaviors have been observed when workers processed the baits, such as licking and scraping their jaws on the surface of the bait pellet, as well as licking and biting fragments of bait pellets, moistening them. Thus, it is concluded that the preparation of baits is different from that of leaves; baits are more processed and can therefore contribute to contaminating workers via insecticides.
Keywords: Ethogram; behavior; leaf-cutter ants; control